How do mangrove forests induce sedimentation? - Kathiresan, K. (2003)
The mangrove forests play a significant role as sediment traps. They reduce tidal flows and induce sedimentation of soil particles at low tide. However, there are no such processes taking place in the non-mangrove areas. Site of Avicennia–Rhizophora interphase is more efficient than Avicennia and or Rhizophora zones, in trapping the sediment by 30, 25 and 20% respectively at low tide as compared to high tide